3-D Biped Robot Walking along Slope with Dual Length Linear Inverted Pendulum Method (DLLIPM). (4th November 2013) - Ali, Fariz; Shukor, Ahmad Zaki Hj.; Miskon, Muhammad Fahmi; Nor, Mohd Khairi Mohamed; Salim, Sani Irwan Md
A new design method to obtain walking parameters for a three-dimensional (3D) biped walking along a slope is proposed in this paper. Most research is focused on the walking directions when climbing up or down a slope only. This paper investigates a strategy to realize biped walking along a slope. In conventional methods, the centre of mass (CoM) is moved up or down during walking in this situation. This is because the height of the pendulum is kept at the same length on the left and right legs. Thus, extra effort is required in order to bring the CoM up to higher ground. In the proposed method, a different height of pendulum is applied on the left and right legs, which is called a dual length linear inverted pendulum method (DLLIPM). When a different height of pendulum is applied, it is quite difficult to obtain symmetrical and smooth pendulum motions. Furthermore, synchronization between sagittal and lateral planes is not confirmed. Therefore, DLLIPM with a Newton Raphson algorithm is proposed to solve these problems. The walking pattern for both planes is designed systematically and synchronization between them is ensured. As a result, the maximum force fluctuation is reduced with the proposed method.